Manajemen Waktu dan Biaya Proyek dengan Sistem Crash Menggunakan Microsoft Project pada Peningkatan Jalan Soko – Karangbinangun - Hidayat, Moch. Diyas Nur; Hepiyanto, Rasio; Dhana, Rio Rahma (Universitas Batanghari Jambi, 2025)
Time and cost management play an important role in the success of a construction project. Therefore, project planning and scheduling must be done carefully before implementation begins. The Soko – Karangbinangun road improvement project faces a number of challenges, especially in terms of time management. In this project, the work that was supposed to start on September 3 according to the contract, was delayed and only started on September 23. This condition has the potential to cause delays in project completion. This study aims to compare the results of theoretical calculations with the factual conditions in the field, and to evaluate the possibility of accelerating the project schedule without sacrificing cost efficiency. The acceleration method used in this study is the overtime system with variations in duration of 1, 2, and 3 hours. Ms. Project is used as a tool to identify the critical path in the project. The results of the analysis show that out of 9 initial work items, there are 8 items included in the critical path. With a variation of 1 hour overtime, the project duration can be accelerated to 68 days, 10 days shorter than the normal duration of 78 days, with a crashing cost of Rp. 1,233,684,874.50 from the normal cost of Rp. 1,229,803,328.00. For 2-hour overtime, the work can be completed in 59 days, 19 days faster than the normal duration, with a crashing cost of Rp. 1,246,809,926.00. While for 3-hour overtime, the project can be completed in 51 days, or 27 days faster than the normal duration, with a crashing cost of Rp. 1,264,842,460.50. From the results of the analysis that have been known, it can be concluded that the 2-hour overtime variation method is more effective to apply.